Dose Requirement for Replacement Therapy in Hemophilia A - Allain, Jean-Pierre (Thrombosis and Haemostasis, 1979)
In order to determine the correlation between different doses of F. VIII and their clinical effect,. 70 children with severe hemophilia A were studied after treatment with single doses of cryoprecipitate. The relationship between plasma F. VIII levels or doses calculated in u/ kg of body weight and clinical results followed an exponential curve. Plasma F. VIII levels of 0.35 and 0.53 u/ml corresponded to 95 and 99% satisfactory treatment, respectively. Similar clinical results were obtained with 20 and 31 u/kg. When the in vivo recovery of F. VIII after lyophilized cryoprecipitate was 0.015 u/ml for each u/kg injected, plasma F. VIII levels of 0.30 and 0.47 u/ml respectively were achieved. Since home treatment is largely based on single infusions of F. VIII, it is suggested that moderate and severe hemorrhages be treated with a dose which will provide a plasma F. VIII level of 0.5 u/ml.